THE ROLE OF MUNICIPAL SCIENCE IN GEOGRAPHY EDUCATION (Web of Teachers: Inderscience Research, 2023)
The country is an important part of geography education. This science is based on the study and understanding of human history and current world powers. The main objective of the country's science is to explain the geographical skills of the world, its economic and social conditions, its natural resources, and the economic and integration processes of countries in a huge area. This article reveals the importance of the country's subjects, their historical history, their methods, and their importance in the current world. Scientific research and historical approaches, geographical information and skills are used in the country. This science, in terms of globalization, is important in studying the cooperation, economic relations and political views of foreign countries. The article also discusses the modern context of the country and the importance of defining, interpreting, and introducing it to important teachings in the study of global views. In the education of the country, it should be appropriate to provide students with experimental teaching aids and programs, to study foreign languages, and to increase their interest and general acceptance of geographical information.